PEMANFAATAN LAHAN PEKARANGAN RUMAH DAN LIMBAH RUMAH TANGGA DALAM MEWUJUDKAN KETAHANAN PANGAN KELUARGA DI KELURAHAN MATAIWOI KOTA KENDARI - L, Mariani; Fausayana, Ine; Sidu, Dasmin; Sarinah, Sarinah; Elvira, Ilian (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2023)
Until now, food security remains a significant issue in Indonesia. In terms of meeting household food needs, the utilization of backyard land can be the best solution in building food security for the community's families. Another issue that needs significant attention is plastic waste, which is a type of non-biodegradable waste that can pollute the environment. This problem is challenging for the general public to address due to a lack of human resources and the necessary information to optimize the system. Therefore, to address the aforementioned issues, the purpose of this community service is to provide training and assistance to community groups in the Mataiwoi Village, Kendari City, as an effort to optimize the use of household backyard and household waste to support Indonesia's waste-free initiative. The implementation of this community service is carried out through lectures, discussions, and demonstrations. The results of this activity include an increase in community knowledge about the utilization of backyard land and household waste, which can be applied in each household's backyard to support food security and improve the well-being of the community as a solution to the problem.